Report of Meeting Researches in Didactics of Mathematics and Computer Sciences: January 27-29, 2017 Budapest, Hungary (Teaching Mathematics and Computer Science, 2017)
The meeting Researches in Didactics of Mathematics and Computer Sciences was held in Budapest, Hungary from the 27th to the 29th of January, 2017 at Eötvös Lorand University. It was organized by the Doctoral School of Mathematical and Computational Sciences of University of Debrecen and the Department of Mathematics Teaching and Education Centre Institute of Mathematics.The 62 participants – including 43 lecturers and 20 PhD students – came from 7 countries, 22 cities and represented 35 institutions of higher and secondary education.